Property Corporation Exit Strategy Planning and the Importance of Contingency Leadership - Deddy Arief Himawan; Wisnu Panggah Setiyono; Hadiyah Fitriyah (International Journal of Social Science and Business, 2023)
This study aims to describe exit strategies in the property development services industry and highlight the importance of implementing contingency leadership in XYZ companies. The focus is on a situation where the decline in apartment sales occurs due to the saturation of the property market and the impact of the Covid-19 pandemic. The main objective of the study is to provide an in-depth understanding of exit strategies in the property development industry and to evaluate the role of contingency leadership in dealing with such situations. This research is a descriptive research with a qualitative approach, which aims to describe and analyze the situation in the property development service industry. The subject of the study is Company XYZ, which represents companies in the property development industry. Data was collected through semi-structured interviews with related parties at Company XYZ. Data is analyzed with steps that include description, data reduction, data presentation, and verification. The results showed that the decline in apartment sales has occurred since 2018 due to the saturation of the property market and the Covid-19 pandemic, as well as the importance of implementing contingency leadership in dealing with the situation. This research provides a new understanding of exit strategies in the property development industry and the mechanisms for selecting them. It can be a basic policy guide for companies in the face of similar challenges. This research has a particular focus on Company XYZ.